The Role of Prayer as Therapy and Advice to Grow Mindfullness During The Quarter Life Crisis of Psychology Students - Rahni Rismawati; Ghazy Agil Saleh; M Najarudin Rizky; Kms Muhammad Arif; Siti Firda Musiyanti (CV. Doki Course and Training, 2025)
Quarter-life-crisis is a feeling of worry experienced by individuals around the age of 20 regarding the uncertainty of their future life regarding relationships, careers and social life. One way to reduce feelings of worry during the quarter-life-crisis requires the individual's ability to gain peace of mind through psychological therapy in the form of spiritual therapy, namely prayer. Prayer is a condition that can provide a feeling of security and peace, when a person's entire body and soul is focused on one thing, namely Allah SWT. This research uses measuring instruments and methods which are qualitative research, using observation and interview data collection methods using 23 interview question items and using the prayer therapy approach method.